On Certain Subclass of Meromorphic Multivalent Functions Associated with Fractional Calculus Operator - Hussein, Sattar K.; Jassim, Kassim A. (Iraqi Journal of Science, 2024)
In this paper, the class of meromorphic multivalent functions of the form by using fractional differ-integral operators is introduced. We get Coefficients estimates, radii of convexity and star likeness. Also closure theorems and distortion theorem for the class , is calculaed.